Improvement of culture conditions for long-term in vitro culture of Plasmodium vivax - Wanlapa Roobsoong (2018)
© 2015 Roobsoong et al. Background: The study of the biology, transmission and pathogenesis of Plasmodium vivax is hindered due to the lack of a robustly propagating, continuous culture of this parasite. The current culture system for P. vivax parasites still suffered from consistency and difficulties in long-term maintenance of parasites in culture and for providing sufficient biological materials for studying parasite biology. Therefore, further improvement of culture conditions for P. vivax is needed. Methods: Clinical samples were collected from patients diagnosed with P. vivax in western Thailand. Leukocyte-depleted P. vivax infected blood samples were cultured in a modified McCoy's 5A medium at 5% haematocrit under hypoxic condition (5% O2, 5% CO2, and 90% N2). Reticulocytes purified from adult peripheral blood were added daily to maintain 4% reticulocytes. Parasites were detected by microscopic examination of Giemsa-stained smears and molecular methods. Results: The effects of culture variables were first analysed in order to improve the culture conditions for P. vivax. Through analysis of the sources of host reticulocytes and nutrients of culture medium, the culture conditions better supporting in vitro growth and maturation of the parasites were identified. Using this system, three of 30 isolates could be maintained in vitro for over 26 months albeit parasite density is low. Conclusions: Based on the analysis of different culture variables, an improved and feasible protocol for continuous culture of P. vivax was developed.